Acute mesenteric ischemia: guidelines of the World Society of Emergency Surgery: a brief radiological commentary - Maria Antonietta Mazzei (World Journal of Emergency Surgery, 2018)
Abstract The aim of this letter is to report some deeper explanations regarding the role of imaging in acute mesenteric ischemia. The correlation between some computed tomography findings and the cause of ischemia as well as other main factors that could condition the computed tomography appearance of this critical issue is also discussed.